Household Food Insecurity Metabolic Syndrome in Women and Nutritional Status of Children Among Urban Indians in Puchong, Selangor - Mohammad Hamad, Hani Jameel (2011)
The main objectives of this study were to determine the status of household food insecurity and its relationships with the risks of metabolic syndrome in women, and the nutritional status of children among urban Indians in Puchong, Selangor, Malaysia. In this cross sectional study, a total of 105 women and an equal number of children were selected based on the Cochran’s formula. The households were selected by convenient sampling guided by the selection criteria that the women’s age must be between 19-49 years with at least one child aged 2.0-18 years, and the women must be neither pregnant nor lactating at recruitment. The data collected included socio-demographic and economic parameters, dietary intake (24-hour diet recall and diet diversity), anthropometric measurements of women and children (weight and height) and waist circumference of the women. Four categories of household food insecurity were determined using the Radimer/Cornell Hunger and Food Insecurity Instrument. These were household food secure and insecure,individual food insecure and child hunger. Blood glucose and lipid profiles, blood pressure and physical activity were also determined among the women. The criteria of the Adult Treatment Panel III of the National Cholesterol Education Program,United States, were used to define metabolic syndrome in the women. The SPSS software was used to analyze both descriptive and inferential statistics among the variables. The NutritionistPro software was used for analyzing the 24-hour diet recall data. The anthropometric data for children were analyzed using the WHO Anthro and WHO AnthroPlus softwares. The majority of the women were housewives with 2-4 children on average, were not receiving public financial aid or supplementary food. Their household monthly mean income was RM 1608.60. This is above the poverty line, which was defined by the Eighth Malaysia Plan (2001) as RM510 per month for a household with 3 children aged between 1-9 years. There were no significant mean differences in the age, marital status, education attainment, employment status, number of children, household size and economic status among the four levels of household food insecurity. Out of the 105 households, only 16.2% were food secure while 24.8% were food insecure, 25.7% individual food insecure and 33.3% showed child hunger status. The mean total energy intake of the women was 1163.54 kcal. None of the age groups for women met the Malaysian Recommended Nutrient Intake (RNI) for the macro- and micronutrients studied. Based on the dietary diversity score, most of the women consumed less than the minimum recommended number of servings for all the food groups. The mean body mass index (BMI) of the women was 28.1 kg/m2,and 66.7% were in the overweight/obese category, while 47.6% were at risk of abdominal obesity. No significant differences were found between the househol food insecurity status and the mean waist circumference, BMI and intake of energy and nutrients among the women. Out of a total of 105 children, there were 40% aged 2.0-4.9 years, 39% 5.0-9.9 years and 21% 10-18 years. Overall, there were 51.4% boys and 48.6% girls. The prevalence of underweight was 23.8%, stunting 27.6%, and 23.8% were overweight/obese for the sexes combined. Among the underweight, the highest percentage (48%) was among the 2.0-4.9 years, while the highest prevalence of stunting (41.4%) and thinness (41.7%) were in the 5.0-9.9 years age group. The average total energy intake for the 2.0-4.9 years, 5.0-9.9 years and 10-18 years (combined sexes) were 960.9 kcal, 869.8 kcal and 1056 kcal, respectively. Only the boys aged 2.0-3.9 years and 4.0-6.9 years met the RNI for energy intake. None of the children of all ages met the RNI for the macro- and micronutrients studied.According to height-for-age z-scores, significant difference (F=3.235, p=0.033) was found in the 5.0-9.9 years between the household ‘food secure (2.55±1.04)’and the rest namely, ‘household food insecure (2.02±0.64)’, ‘individual food insecure (1.26±0.48)’ and ‘child hunger (1.72±0.41)’. Similarly, for weight-for-age z-scores,significant mean differences (F=3.069, p=0.039) were shown in the 2.0-4.9 years between the ‘food secure (-2.93 ± 3.94)’ and the ‘individual food insecure (0.36 ± 2.44)’and ‘child hunger (0.21 ± 1.90)’ groups. The chi-square test revealed a significant association (2=21.901, p=0.001) between the BMI-age z-scores categories and the household food insecurity levels. There was also evidence of a significant association between the weight-for age z score categories in the 2.0-4.9 years and the four levels of household food insecurity (2=12.885, p=0.045)The overall prevalence of metabolic syndrome among the women was 9.5%. The prevalence of women with the risk factors of metabolic syndrome were as follows:high density lipoprotein cholesterol (61.9%), waist circumference (47.6%), triglycerides (13.3%), blood pressure (9.5%) and blood glucose (5.7%). However,there were no significant differences between the presence of metabolic syndrome in the women (having 3 risks and above) and the levels of household food insecurity.Logistic regression results showed that older women (crude OR=1.069, CI=1.00- 1.14; adjusted OR=1.118, CI=1.01-1.24) and women with higher BMI (crude OR=1.283, CI=1.157-1.423; adjusted OR=1.325, CI=1.17-1.50) had an increased risk of abdominal obesity. Unemployed status was significantly (crude OR=2.471, CI=1.10-5.54; adjusted OR=2.823, CI=1.01-7.88) more likely to have high density lipoprotein cholesterol than employed women. On the other hand, those who had increased intake of fruits (crude OR=0.319, CI=0.11-0.93) and higher dietary diversity scores (crude OR=0.835, CI=0.74-0.95) were significantly more likely to have higher HDL-cholesterol.In summary, the majority of the Indian households in Puchong in this study showed different levels of food insecurity. Young children from food secure households had significantly better nutritional status than those from food insecure households. Dietary intake was not found to be significantly different among the children from households of various food insecurity status. Majority of the women were overweight/obese and showed other risk factors of metabolic syndrome. The prevalence of metabolic syndrome was not significantly associated with household food insecurity status. Dietary intake of the women was also not found to have a significant association with household food insecurity levels. It is recommended that future studies include qualitative approaches, more sensitive methods of dietary assessment, and a larger sample size, in order to better define the socio-cultural aspects affecting household food insecurity among urban low to middle income households in Malaysia.